A multicomponent molecular approach to artificial photosynthesis-the role of fullerenes and endohedral metallofullerenes - Rudolf, Marc; Kirner, Sabrina; Guldi, Dirk Michael (Chemical Society Reviews, 2016)
In this review article, we highlight recent advances in the field of solar energy conversion at a molecular level. We focus mainly on investigations regarding fullerenes as well as endohedral metallofullerenes in energy and/or electron donor-acceptor conjugates, hybrids, and arrays, but will also discuss several more advanced systems. Hereby, the mimicry of the fundamental processes occurring in natural photosynthesis, namely light harvesting (LH), energy transfer (EnT), reductive/oxidative electron transfer (ET), and catalysis (CAT), which serve as a blue print for the rational design of artificial photosynthetic systems, stand at the focalpoint. Importantly, the key processes in photosynthesis, that is, LH, EnT, ET, and CAT, define the structure of this review with the only further differentiation in terms of covalent and non-covalent systems. Fullerenes as well as endohedral metallofullerenes are chosen by virtue of their small reorganization energies in electron transfer processes, on the one hand, and their exceptional redox behaviour, on the other hand.
CRIS-Team Scopus Importer:2023-03-07